Previous use of Statins and Atrial Electrical Remodeling in Patients with Cryptogenic Stroke - Acampa, Maurizio; Lazzerini, Pietro E.; Guideri, Francesca; Tassi, Rossana; Lo Monaco, Andrea; Martini, Giuseppe (Cardiovascular & Haematological Disorders - Drug Targets, 2017)
Background: In the general population the leading cause of cardioembolic stroke is atrial fibrillation (AF). A silent AF is also the possible cause of many cryptogenic strokes. P wave dispersion (PWD), a predictor of AF, has been proposed as a marker of silent AF occurrence in these strokes. PWD correlates with high-sensitive C-reactive protein levels reflecting the role of inflammation in promoting a slowed and inhomogeneous atrial conduction. Statins have a multitude of additional effects beyond lipid lowering, in particular anti-inflammatory effects that may influence atrial conduction. Objective: The aim of this study was to evaluate the effects of previous statin use on PWD in patients with cryptogenic stroke, in order to highlight a possible role for statins in preventing atrial conduction alterations that predispose to AF. Method: We enrolled 131 patients (67 males, 64 females; mean age 69±13 years) with cryptogenic stroke. All patients underwent neuroimaging examination, arterial ultrasound examination, echocardiography and ECG. PWD was measured in all subjects. Results: Patients previously treated with statins (n: 34) had lower PWD and P index values in comparison with no-statin group (41.7±12.2 vs 48.7±15.2 ms, p=0.01, and 14.2±3.7 vs 16.5±5.3 ms, p=0.02, respectively). Conclusions: Our results show lower PWD values in cryptogenic stroke patients previously treated with statins. These findings provide support to the hypothesis that statins may play a role in modulating atrial electrophysiological and structural properties, preventing the occurrence of a slowed and heterogeneous atrial conduction and finally, reducing the occurrence of AF.
Keywords: cryptogenic stroke